Immunogenicity of adjuvanted plant-produced SARS-CoV-2 Beta spike VLP vaccine in New Zealand white rabbits. Issue 13 (24th March 2023) - O'Kennedy, Martha M; Abolnik, Celia; Smith, Tanja; Motlou, Thopisang; Goosen, Kruger; Sepotokele, Kamogelo M; Roth, Robyn; du Preez, Ilse; Truyts, Alma; Stark, Hester C; Magwaza, Martin; Mahanjana, Osborn; et al.
Highlights: SARS-CoV-2 virus-like particles (VLPs) successfully assembled in plants. VLPs based on a SARS-CoV-2 Beta (B.1.351) variant of concern (VOC) Beta VLPs elicit robust antibodies which cross-neutralise Delta and Omicron VOCs. The potential of local vaccine development capability demonstrated. VLP vaccine based on VOCs relevant to the African continent. Abstract: The outbreak of the SARS-CoV-2 global pandemic heightened the pace of vaccine development with various vaccines being approved for human use in a span of 24 months. The SARS-CoV-2 trimeric spike (S) surface glycoprotein, which mediates viral entry by binding to ACE2, is a key target for vaccines and therapeutic antibodies. Plant biopharming is recognized for its scalability, speed, versatility, and low production costs and is an increasingly promising molecular pharming vaccine platform for human health. We developed Nicotiana benthamiana -produced SARS-CoV-2 virus-like particle (VLP) vaccine candidates displaying the S-protein of the Beta (B.1.351) variant of concern (VOC), which triggered cross-reactive neutralising antibodies against Delta (B.1.617.2) and Omicron (B.1.1.529) VOCs. In this study, immunogenicity of the VLPs (5 µg per dose) adjuvanted with three independent adjuvants i.e. oil-in-water based adjuvants SEPIVAC SWE TM (Seppic, France) and "AS IS" (Afrigen, South Africa) as well as a slow-release synthetic oligodeoxynucleotide (ODN) adjuvant designated NADA (Disease Control Africa, South Africa) were evaluated in New Zealand white rabbits and resulted in robust neutralising antibody responses after booster vaccination, ranging from 1:5341 to as high as 1:18204. Serum neutralising antibodies elicited by the Beta variant VLP vaccine also showed cross-neutralisation against the Delta and Omicron variants with neutralising titres ranging from 1:1702 and 1:971, respectively. Collectively, these data provide support for the development of a plant-produced VLP based candidate vaccine against SARS-CoV-2 based on circulating variants of concern.